2009
DOI: 10.1163/157075509x12499949744306
|View full text |Cite
|
Sign up to set email alerts
|

Reduced egg laying caused by a male accessory gland product opens the possibility for sexual conflict in a simultaneous hermaphrodite

Abstract: Promiscuity, sperm storage and internal fertilization enhance sperm competition, which leads to sexual confl ict whenever an advantageous trait for sperm donors is harmful to recipients. In separate-sex species, such confl icts can severely impact the evolution of reproductive characteristics, physiology and behaviours. For simultaneous hermaphrodites, the generality of this impact remains unclear and underlying mechanisms remain largely unexplored. In the hermaphrodite Lymnaea stagnalis several previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 25 publications
(31 reference statements)
6
42
0
Order By: Relevance
“…The finding that Ovipostatin reduces egg mass production in the recipient corroborates earlier work indicating that substances in the semen may influence egg laying [13][14][15] . By transferring biologically relevant amounts (see 3.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The finding that Ovipostatin reduces egg mass production in the recipient corroborates earlier work indicating that substances in the semen may influence egg laying [13][14][15] . By transferring biologically relevant amounts (see 3.…”
Section: Discussionsupporting
confidence: 88%
“…Although this procedure here is shown using the prostate gland extract, the effect of a single purified seminal fluid protein can also be tested following the same procedure. Obviously, in such tests it is always crucial to include proper controls (sham treatments) to ensure that the procedure and/or the carrier medium do not affect the parameters in questions 14,16 . Using this method, it has already been shown that there is a single seminal fluid protein, namely Ovipostatin, that mediates a reduction in egg laying 14,16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations